Revitalizing health for all case studies of the struggle for comprehensive primary health care - Labonte, Ronald N.; Sanders, David 1945-; Packer, Corinne 1967-; Schaay, Nikki (Toronto Ottawa University of Toronto Press International Development Research Centre, 2017)
"The concept of comprehensive primary health care focuses on health system efforts to improve equity in health care access, community empowerment, participation of marginalized groups, and actions on the social determinants of health. Despite its existence since the late 1970s very few studies have been able to highlight the outcomes of this concept, until now. Revitalizing Health for All examines thirteen cases of efforts to implement CPHC reforms from around the globe including Australia, Brazil, Democratic Republic of Congo, Iran, South Africa, and more. The findings presented in this volume originate from an international action-research set of studies that utilized triads of senior and junior researchers and knowledge users from each country's public health system. Primary health care reform is an important policy discourse both at the national level in these countries and in the global conversations, and this volume reveals the similarities among CPHC projects in diverse national contexts. These similarities provide a rich evidence base from which future CPHC reform initiatives can draw, regardless of their country."--Provided by publisher.
Includes bibliographical references and in
Keywords: Primary health care; Medicine, Preventive